A global bibliometric and visualized analysis in the status and trends of subchondral bone research. Issue 22 (29th May 2020) - Mao, Xingjia; Chen, Chenglong; Wang, Bin; Hou, Jie; Xiang, Chuan
Abstract: Background: Structural and functional changes in subchondral bone have been recognized as a key factor in the development of related disease, and subchondral bone may be a new target for the treatment of osteoarthritis. The purpose of our present study is to investigate the global status and trends of subchondral bone research. Method: Publications related to the studies of subchondral bone from 1993 to 2018 were retrieved from the Science Citation Index-Expanded Web of Science database. The data source was studied and indexed by using bibliometric methodology. For visualized study, bibliographic coupling analysis, co-authorship analysis, co-citation analysis, co-occurrence analysis and the analysis of publication trends in subchondral bone research were conducted by VOS viewer and GraphPadPrism 5 software. Results: A total of 4780 publications were included. There is an increasing trend of the relative research interests and number of publications per year globally. The cumulative number of publications about subchondral bone research followed the logistic growth model . The USA made the highest contributions to the global research with the most citations, the highest H-index, and the most total link strength, while Denmark had the highest average citation per item. The journal Osteoarthritis and Cartilage had the largest publication number. Boston University is the most contributive institution. Studies could be divided into 4 clusters: "Mechanism research", "Animal study", "Clinical study" and "Pathological features". Less efforts were put into clinical study. Conclusion: The number of publications about subchondral bone research would be increasing in the next years based on the current global trends. Attention should be drawn to the latest popular research, including "Mesenchymal stem-cells", "Autologous chondrocyte implantation", "Microfracture" and "Pain". Therefore, more and more efforts will be put into mechanism research on subchondral bone, which may inspire new clinical treatments for osteoarthritis and other related diseases based on subchondral bone.